Decision Support System For Determining the Best Teacher at Private Ballerina Elementary School using the Simple Additive Weighting (SAW) Method - Dewi, Maimuna; Wahyuni , Dewi; Mughnyanti, Mayang (Journal of Technology and Computer, 2024)
At this time the utilization of science and technology is developing very quickly and producing new innovations that must be balanced with the ability to adapt to these technologies. One of these fields is a decision support system that can assist in decision-making. SDS Balerina is an educational institution in Medan. SDS Balerina has conducted assessment activities to determine the best teacher, but the assessment has not produced maximum results because all teachers are said to be good, all of them are equal, no one distinguishes their degrees, the results of the assessment are not announced to the teacher concerned, only the principal knows about it and does the assessment. However, what determines this decision-making is the decision-maker himself because the system is only an alternative decision. The final decision is still determined by the decision maker, namely the school principal.